Penerapan Mesin Spinner Peniris Minyak dan Perbaikan Kemasan Produk pada UMKM Keripik di Desa Kemetul, Kecamatan Susukan, Kabupaten Semarang - Kusumaningtyas, Ratna Dewi; Prasetiawan, Haniif; Bahlawan, Zuhriyan Ash Shiddieqy; Widyastuti, Catur Rini; Imani, Nadya Alfa Cahaya; Rachmadi, Moch Faizal; Jannah, Reni Ainun; Ichwan, Rizky; S., Syifa Azzahra Putri (Universitas Negeri Semarang, 2025)
Desa Kemetul, Kecamatan Susukan is one of 208 villages developed into tourist villages in Kabupaten Semarang. Desa Kemetul is an area rich in agricultural products. Cassava and taro crops in this village are often processed into chips and serve as a source of income for residents. Common problems that often arise with chip products are the remaining oil content in the chips after frying and inappropriate product packaging. Thus, it reduces the quality and shelf life of the chip product. This Community Service activity focused on improving the chip production process at the Jago MSME in Desa Kemetul. The activity began with discussions and coordination with the local government and Jago MSME owner as partner. The activities included the implementation of an oil spinner machine and improved packaging with a portable sealer and silica gel. The application of appropriate technology can improve the chips quality and shelf life of products. It as well increases production capacity, profit potential, and support the development of Desa Kemetul as a tourist village.